“Stepchildren of free Russia”: collective consciousness of orthodox priests during russian revolution - Gleb Zapalsky (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2020)
This paper is devoted to numerous manifestations of social activity of Orthodox priests in Russia in 1917?1918: priests’ unions, priests’ assemblies, letters to authorities, articles in media. The author of the article uses public texts which help to study mass (rather than elite) ideas, most commonly encountered in the public space. These texts highlight practical, even down-to-earth problems, their rhetoric and emotions reach a grotesque level with events of the revolution in the background. But collective consciousness of priests, their thoughts about their own community are implicitly manifested in these texts as well. This was the result of collective activity of the rallied priests. The author comes to the conclusion that the collective consciousness of priests was almost non-manifested in the public space during the revolution. We often meet elements of their professional consciousness, the contrast of their community and proximate communities (monk clergy, lower clerics), the need to be seen as ordinary people and citizens, to get a right of choice, e.g. to choose a secular work or even to take off their rank without any sanction. The pastoral consciousness, a feeling of priest’s high vocation, his responsibility, the impossibility to leave his service were also manifested brightly. It is hard to make a strict distinction between the professional and the pastoral consciousness, but it is clear that the choice between them became sharper during the events of the Russian Revolution.